The Accidental Discovery of a Rare and Diagnostically Challenging Antibody, Anti Diegoa. (9th November 2022) - Irfan, A; Jiles, C; Hamdan, H
Abstract: Introduction/Objective: Anti Diego a antibody (DiA) is a rare antibody, associated with severe hemolytic disease of the newborn. It is seen in American Indians and Asians of Mongoloid descent. Only 2.6% of Hispanics and <0.01% of Caucasians and African Americans have this antibody, making it challenging to diagnose. We present a case of a DiA discovered accidentally. Methods/Case Report: A 31-year-old G4P3 Hispanic female at 35 weeks 5 days of gestation presented with limited prenatal care and gestation complicated by chronic deep vein thrombosis, on enoxaparin. Her gestational history was significant for Anti-E Antibody (Anti-E) with a gel titer of 1:8 during her second gestation. During her current pregnancy her Anti-E Ab gel titer was 1:32 and an Anti-c Antibody (Anti-c) was also detected. R1R1 panel was used to detect further antibodies since the patient was Anti-E and Anti-c. The initial gel panel could not rule out Duffy Antibody (FyA) and Kidd Antibody (JkB). Two R1R1 panels had already been cross matched and both were compatible. A second gel panel showed Kell antigen (KpA), FyA and JkB, all with a +2 positivity in a R1R1 cell panel (Cell X). Antigen typing labelled the patient as JkB+ and FyA-. One compatible unit was FyB- making FyA- unlikely. One of the cross matched compatible units was FyA+. An additional homozygous R1R1 cell was negative for FyA. Therefore FyA- was ruled out. The positivity on Cell X was then thought to be KpA. A solid phase panel (Cell Y) was conducted and was positive, supporting KpA as the causative factor. A decision was made to repeat our test using the initial patient sample plus a CBC tube. This demonstrated KpA negativity, negating KpA as the causative factor. However the Cell Y positivity in the solid phase panel was still questionable. DiA, a low frequency antibody is also found on this cell. This led to further testing. Another R1R1 cell showed +3 positivity for DiA. Antibody identification confirmed this as DiA with a titer of 2. The patient underwent induction of labor and delivered a healthy neonate. Results (if a Case Study enter NA): N/A Conclusion: Since DiA is located in the same panel as KpA, the positive result was presumed to be secondary to KpA. However repeat testing demonstrated KpA negativity and thereby unmasked DiA as the culprit.